2018
DOI: 10.3892/etm.2018.6377
|View full text |Cite
|
Sign up to set email alerts
|

Role of ALK5/SMAD2/3 signaling in the regulation of NOX expression in cerebral ischemia/reperfusion injury

Abstract: Nicotinamide adenine dinucleotide phosphate oxidase (NOX)-derived reactive oxygen species (ROS) serve an important role in cerebral ischemia/reperfusion (I/R) injury. However, the mechanism by which ROS generation is regulated has not yet been fully elucidated. The present study aimed to explore the role of transforming growth factor-β signaling in ROS generation. Sprague Dawley rats were subjected to I/R injury and PC-12 cells were transfected with small interfering RNA against activin receptor-like kinase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(47 reference statements)
2
4
0
Order By: Relevance
“…B, ROS production measured by flow cytometry in the indicated groups, n = 3. 40 In line with previous studies, we observed in this study that the ALK5/Smad2/3 pathway was activated, as evidenced by elevated levels of ALK and p-Smad2/3 which induced the upregulation of Nox4 in I/R injury, both in vivo and in vitro. C, Western blot analysis for the protein expression of NLRP3, ASC, Caspase-1, and IL-1β and bar graph showed quantification, n = 3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…B, ROS production measured by flow cytometry in the indicated groups, n = 3. 40 In line with previous studies, we observed in this study that the ALK5/Smad2/3 pathway was activated, as evidenced by elevated levels of ALK and p-Smad2/3 which induced the upregulation of Nox4 in I/R injury, both in vivo and in vitro. C, Western blot analysis for the protein expression of NLRP3, ASC, Caspase-1, and IL-1β and bar graph showed quantification, n = 3.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the relationship between ALK5/Smad2/3 signaling pathway and the occurrence of oxidative stress was identified by Lou et al who revealed that ALK5/Smad2/3 pathway was associated with ROS generation through targeting Nox4/Nox2 activity in cerebral I/R injury. 40 In line with previous studies, we observed in this study that the ALK5/Smad2/3 pathway was activated, as evidenced by elevated levels of ALK and p-Smad2/3 which induced the upregulation of Nox4 in I/R injury, both in vivo and in vitro. In addition, knockdown of ALK5 with si-RNA downregulated ALK5 and p-Smad2/3 levels, ultimately leading to a remarkable decrease in the levels of Nox4 upon H/R injury stimuli, further demonstrating that Nox4 was modulated by the ALK5/Smad2/3 pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nox4-induced oxidative stress is a pathological feature of cerebral hypoxia-ischemia 53,54 and Rictor/mTorc2 deficiency has been shown to aggravate HI-induced injury in various models 55,56 . Based on this knowledge, we aimed to verify the involvement of the Parp3-mTorc2 axis in vivo in normal mice and in response to HI.…”
Section: Enhanced Nox4-induced Ros In Parp3-deficient Cells Cause Incmentioning
confidence: 99%
“…However, as soon as angiogenesis and subsequent blood perfusion, ischemic reperfusion injury occurs 7,8. It means that oxidative stress occurs in the ischemia tissue and injuries random skin flaps, accompanied with cell apoptosis 9,10. Previous studies have demonstrated that promoting angiogenesis, and suppressing oxidative stress and apoptosis can enhance random skin flap survival.…”
Section: Introductionmentioning
confidence: 99%